Design and modeling of dispersion-engineered all-chalcogenide triangular-core fiber for mid-infrared-region supercontinuum generation - Karim, Mohammad Rezaul; Ahmad, Harith; Rahman, B.M. Azizur (Optical Society of America, 2018)
An ultrabroadband mid-infrared supercontinuum (SC) source has been designed and modeled using a 10-mm-long all-chalcogenide triangular-core fiber (TCF). The TCF structure can be fabricated from Ge 11.5 As 24 Se 64.5 chalcogenide glass as a core and Ge 11.5 As 24 S 64.5 chalcogenide glass for its cladding running along the length of the fiber instead of air holes. Assuming the pump operates at 4 μm, the TCF is optimized by varying its side length using both anomalous-dispersion and all-normal-dispersion SC generation. Mid-infrared-region SC spectral broadening spanning beyond 15 μm could be generated with a low peak power of 3 kW by the proposed TCF structure optimized with varying its side length between 7 and 8 μm in anomalous-dispersion pumping. On the other hand, the TCF side length has to be decreased to 5.5 μm and below to optimize it for pumping in all-normal-dispersion-region SC generation. A coherent flat-top SC evolution in the mid-infrared region of up to 7 μm could be observed by this design with the same pump peak power and pulse duration applied before. The ultrawide optical bandwidth obtained by the proposed TCF design can be an effective tool for mid-infrared-region applications such as optical coherence tomography, molecular fingerprint spectroscopy, and biomedical imaging.